Transfer of training in sports - Bondarchuk, A. P. (Ultimate Athlete Concepts, 2007)
Dr. Anatoly Bondarchuk is renowned as an athlete (1972 Olympic Champion and European Champion in the hammer throw as well as a former World Record Holder) and Mr. Bondarchuk's coaching credentials are virtually unprecedented in the sport of Athletics. Dr. Bondarchuk is a Doctor of Pedagogical Science ( University of Kiev ) and his research into technique and high-performance training methods formed the basis for many of the common techniques and practices used by the world's top athletes today. Mr. Bondarchuk developed the USSR National Team throws program from 1976 to 1992 from which he produced numerous World and Olympic Champions in the Hammer, Discus and Shot Put. He has authored 11 books and 195 articles in his areas of expertise. A common focus is training to maintain performance and technique. Since 1992 he has been coaching for Portugal and Kuwait. Mr. Bondarchuk's athletes, while members of the USSR National Team, broke 12 World Records, and still hold the current world record in the hammer throw. His athletes won all hammer throw medals in 4 consecutive non-boycotted Olympic Games. (Klappentext)